Excitations and finite-size properties of an integrable supersymmetric electronic model - Malvezzi, André Luiz [UNESP]; Martins, M. J. (Amer Physical Soc, 2010)
We investigate the bulk and finite-size properties of an integrable extension of the Hubbard model with a free parameter gamma related to the quantum deformation of the superalgebra sl (2 vertical bar 2)((2)). The Bethe ansatz solution is used to determine the ground state and the nature of the spin and charge excitations. As gamma -> 0 the charge dispersion relation for low momenta crossover from linear to parabolic foreseeing a change from antiferromagnetic to ferromagnetic behavior. The study of the finite-size corrections to the spectrum reveals us that the underlying conformal theory has central charge c=-1 and a related effective central charge c(ef) = 2 as well as critical exponents depending on the parameter gamma. We note that exact results at the isotropic point gamma=0 can be established without recourse to the Bethe ansatz solution.